Peraturan perundangan perwakafan: undang undang nomor 41 tahun 2004 tentang wakaf... - INDONESIA,_Undang_Undang_Peraturan_dan_Sebagainya (Dirjend Bimas Islam Depag, 2006)
oen, c.1-49/stoc1,c.1-49=c.1/oen, c.50-51